2021
DOI: 10.1071/wr20186
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic changes in energy expenditure and resting behaviour of humpback whale mother–calf pairs examined using unmanned aerial vehicles

Abstract: Context Baleen whale calves rapidly increase in size and improve locomotion abilities, while on their low-latitude breeding ground, allowing them to undertake a successful migration to high-latitude feeding grounds. Aims We investigated energy expenditure and resting behaviour of humpback whale (Megaptera novaeangliae) mother–calf pairs in regard to changes in calf length on an undisturbed breeding/resting ground off Exmouth Gulf, Western Australia. Methods Data were collected from August to October in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 60 publications
3
8
0
Order By: Relevance
“…Our findings are consistent with the previous studies done on humpback whales calves in their breeding grounds (Cartwright & Sullivan 2009, Tyson et al 2012, Ejrnaes & Sprogis 2021. Of the 29 studied calves, we found that 4 out of the 10 analyzed dive metrics varied significantly with age.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are consistent with the previous studies done on humpback whales calves in their breeding grounds (Cartwright & Sullivan 2009, Tyson et al 2012, Ejrnaes & Sprogis 2021. Of the 29 studied calves, we found that 4 out of the 10 analyzed dive metrics varied significantly with age.…”
Section: Discussionsupporting
confidence: 93%
“…However, since we could record dives only on two C1 calves, great care should be taken in generalizing the present results. Nevertheless, these findings suggest that older calves showed higher swimming and breathing abilities, as previously found in humpback whales (Cartwright & Sullivan 2009, Ejrnaes & Sprogis 2021 and observed in right whales (Cusano et al 2019, Dombroski et al 2021). As suggested in previous studies, neonate calves have limited lung capacity as they are still learning to manage their breathing cycle and buoyancy.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This is, however, not the case in other locations in Australia (e.g., Sprogis et al, 2020), and around the world (e.g., Fiori et al, 2019), where swimming with calves occurs, even in areas where it has been advised against. It is of great importance to limit disturbance on mother-calf pairs as they are the most sensitive to disturbance (Sprogis et al, 2020) and, over extended periods of time, increases in energy expenditure could become biologically significant for mothers with a dependent calf (Cartwright and Sullivan, 2009;Ejrnaes and Sprogis, 2021). Thus, in Hervey Bay it is of importance to retain best practice guidelines on not swimming with calves to reduce disturbance to the whales, but also to avoid injury to humans from high-risk situations with mother and calves (as documented in Sprogis et al, 2017Sprogis et al, , 2020Fiori et al, 2019;Barra et al, 2020;Hoarau et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The opposite was observed on their lower latitude breeding grounds, where 32 humpback whale calves (TL range: 4.14-7.76 m, thus classified as n = 30 post-neonate, n = 2 neonate, see Irvine et al, 2017a) increased their TL, but not their body condition (Christiansen et al, 2016). Calves may first prioritize investing energy towards growth on the breeding grounds to reduce heat loss via reducing their surface area to volume ratio, to enhance breath holding ability (Ejrnaes and Sprogis, 2022), and to avoid predation by killer whales (Orcinus orca) and sharks (Pitman et al, 2015). Then, as they enter their high latitude foraging grounds, they begin to invest more energy toward fat and blubber storage.…”
Section: Variation In Body Condition Increase Amongst Reproductive Cl...mentioning
confidence: 99%